Consuming with care: insights into ethical consumption in Iran - Karimzadeh, Sara (Frontiers in Sustainability, 2025)
This study examines the meanings and practices of ethical consumption in Iran, enriching dominant narratives that link ethical consumption primarily to institutional frameworks or environmental discourses. It argues that ethical considerations are instead embedded in local cultural, spiritual, and social norms. The research draws on 19 in-depth qualitative interviews with urban residents in the midsized city of Urmia. A thematic analysis was employed to understand participants' practices across three stages of consumption: pre-consumption, consumption, and post-consumption. In the pre-consumption stage, structural constraints—such as limited access to reliable information and economic precarity—define the boundaries of ethical choices. The consumption stage is primarily influenced by sufficiency-oriented ethic through the avoidance of heyf-o-meyl (wastefulness and unnecessary consumption), reflecting values rooted in traditional and cultural teachings. In the post-consumption stage, the practice of ehsan kardan (acts of care and generosity) emerged as a key form of ethical divestment that minimizes waste and supports others in need. The study reveals that participants conceptualize ethical consumption through human-centered values—such as care, responsibility, and generosity—rather than through environmentalism or formal regulation. The results contribute to the literature on sustainable consumption by highlighting culturally embedded, locally meaningful forms of ethical engagement that constitute a moral micro-economy.